The genus Pronephrium C. Presl (Thelypteridaceae) from Bangladesh (Bangladesh Journal of Plant Taxonomy, 2007)
The paper deals with the genus Pronephrium C. Presl of the family Thelypteridaceae and includes five species, namely P. articulatum (Haulst. & Moore) Holtt., P. lakhimpurensis (Rosenst.) Holtt., P. nudatum (Roxb. ex Griff.) Holtt., P. parishii (Bedd.) Holtt., and P. triphyllum (Sw.) Holtt. from Bangladesh. Descriptions of the species with artificial key, illustrations, distribution and short notes with conservation measures are given here. Key words: Pronephrium, Thelypteridaceae, Pteridophyte, Bangladesh DOI: 10.3329/bjpt.v14i1.521 Bangladesh J. Plant Taxon. 14(1): 37-45, 2007 (June)